Otelde Bir Gun A Day At Hotel : A Day At Hotel - Rita Ender (Istanbul; Zilberman Gallery, 2018)
Artists: Basak Bugay, Hera Buyuktasciyan, Can Kucuk, Sant Mengucek, Erinc Seymen. Exhibition @Zilberman Gallery from Sep-Nov 2018.
English; Turkish
Keywords: N4390-5098 Visual Arts. Exhibitions; Turkey